2020
DOI: 10.1590/0103-3352.2020.33.234299
|View full text |Cite
|
Sign up to set email alerts
|

Governabilidade e lógica de designações no Ministério Público Federal: os “procuradores políticos profissionais”

Abstract: Resumo: Este artigo analisa o papel das designações no contexto do Ministério Público Federal (MPF). Apresenta duas novidades: i) a utilização de uma literatura para pensar o contexto do MPF como espaço de ação regido por regras formais e informais, marcado pelo conflito e a disputa pelo poder; e ii) a análise de um inédito banco de dados sobre a carreira dos procuradores-gerais da República que ocuparam o cargo desde 1988, pensado como registro da ação realizada pelos indivíduos. Como o aspecto da governabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
0
3
0
4
Order By: Relevance
“…Before analyzing the research findings, it is worth highlighting an aspect that, while outside the focus of this study, may help explain the communicational action developed by these organizations on social media: MPF members are often in a position to articulate career political strategies when carrying out inquiries and lawsuits with repercussions inside and outside the institution (Viegas, 2020), so it is likely that this is replicated in the area of communication on social media. This heightened level of personalism among MPF members affects the way in which communication might accomplish the accountability of the institution as a whole.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Before analyzing the research findings, it is worth highlighting an aspect that, while outside the focus of this study, may help explain the communicational action developed by these organizations on social media: MPF members are often in a position to articulate career political strategies when carrying out inquiries and lawsuits with repercussions inside and outside the institution (Viegas, 2020), so it is likely that this is replicated in the area of communication on social media. This heightened level of personalism among MPF members affects the way in which communication might accomplish the accountability of the institution as a whole.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…By subjecting this finding (reduced content) to specific (conventional) content analysis, we found that the MPF, in tandem with the National Association of Federal Prosecutors (Associação Nacional dos Procuradores da República, or ANPR), operates as a "spokesperson" for routine matters, but also for those linked to the interests of MPF members, especially functional prerogatives. The ANPR is a private entity advocating the corporate interests of MPF members (Viegas, 2020).…”
Section: Figurementioning
confidence: 99%
“…Ao submeter essa constatação (conteúdo reduzido) à análise de conteúdo específica (convencional), verificamos que o MPF, em combinação com a Associação Nacional dos Procuradores da República (ANPR), atua como um "porta-voz" de assuntos de atuação rotineira, mas também aqueles ligados a interesses dos membros do MPF, especialmente prerrogativas funcionais. A ANPR é uma entidade privada que defende os interesses corporativos dos membros do MPF (Viegas, 2020).…”
Section: Figuraunclassified
“…Antes de analisar os achados da pesquisa, cabe destacar um aspecto que, embora escape do foco do presente estudo, pode ajudar a explicar a ação comunicacional que os órgãos desenvolvem nas redes sociais: os integrantes dos MPF são capazes de mobilizar estratégias políticas de carreira ao realizar inquéritos e ações que têm reflexos dentro e fora da instituição (Viegas, 2020), sendo então provável que isso se repita na área de comunicação em redes sociais. Essa maior personalização dos membros dos MPF afeta a forma como a comunicação pode realizar a accountability do conjunto da instituição.…”
Section: Discussão E Conclusõesunclassified
See 1 more Smart Citation